Mapping Dye-sensitised Solar Cells Research in India : A Scientometric Study - Dutt, Bharvi; Kumar, Suresh (DESIDOC Journal of Library & Information Technology, 2018)
The paper examines 718 dye sensitised solar cell (DSSC) research articles published by Indian scientists during 2011-15, which were indexed in Web of Science. It looked into the entire gamut of research performance by performing sectors, institutions, multifarious collaborative aspects, co-authorship and citations etc. Private universities figure among top performing institutions and nano-related aspects dominated DSSC research. DSSC research by Indian researchers was found to be in tune with the mainstream science in the area as about 90 per cent of the research found place in international journals published from USA, the UK and other advanced countries of Europe with respectable impact factor.